The associations between diabetes distress and self-efficacy, medication adherence, self-care activities and disease control depend on the way diabetes distress is measured: Comparing the DDS-17, DDS-2 and the PAID-5. (August 2018) - Chew, Boon-How; Vos, Rimke C.; Pouwer, Frans; Rutten, Guy E.H.M.
Highlights: There are several instruments to measure diabetes distress (DD) in clinical practice and research. Associations of DD with outcomes are influenced by confounders and depend on the instruments. Findings call for a judicious use of different DD measures in clinical practice and research. Abstract: Aims: To examine whether diabetes distress (DD), when measured by three different instruments, was associated differently with self-efficacy, self-care activity, medication adherence and disease control in people with Type 2 diabetes mellitus. Methods: A cross-sectional study in three health clinics. DD was assessed with the 17-item Diabetes Distress Scale, the 2-item DDS-2 (DDS-2) and the 5-item Problem Areas in Diabetes Scale (PAID-5). Dependent variables included self-efficacy, self-care activities, medication adherence, HbA1c, systolic and diastolic blood pressure (SBP, DBP). Multiple linear and logistic regression were used in analyses. Results: In total 338 participants (56% women), with a mean age of 61 years and diabetes duration of 9.8 years, were included. DDS-2 was an independent determinant of SBP (β = 1.89, 95% CI 0.14, 3.64), DBP (β = 1.19, 95% CI 0.16, 2.21) and blood pressure target (OR = 2.09, 95% CI 1.12, 3.83). PAID-5 was an independent determinant of medication adherence (adjusted β = −0.05, 95% CI −0.08, −0.01) and self-care activities (OR = 0.50, 95% CI 0.26, 0.99). Conclusions: Associations of DD with important aspects of diabetes care are substantially influenced by confounders and depend on the way DD is measured. Our findings call for a judicious use of different DD measures in clinical practice and research. The study is registered onClinicalTrials.gov (NCT02730754).